A systematic review with meta-analysis of biomarkers for detection of pulmonary arterial hypertension. Issue 2 (30th May 2022) - Smits, A. Josien; Botros, Liza; Mol, Marijke A.E.; Ziesemer, Kirsten A.; Wilkins, Martin R.; Vonk Noordegraaf, Anton; Bogaard, Harm Jan; Aman, Jurjan
Rationale: The blood is a rich source of potential biomarkers for the diagnosis of idiopathic and hereditary pulmonary arterial hypertension (iPAH and hPAH, referred to as "PAH"). While a lot of biomarkers have been identified for PAH, the clinical utility of these biomarkers often remains unclear. Here, we performed an unbiased meta-analysis of published biomarkers to identify biomarkers with the highest performance for detection of PAH. Methods: A literature search (in PubMed, Embase.com, Clarivate Analytics/Web of Science Core Collection and Wiley/Cochrane Library) was performed up to 28 January 2021. Primary end points were blood biomarker levels in PAH versus asymptomatic controls or patients suspected of pulmonary hypertension (PH) with proven normal haemodynamic profiles. Results: 149 articles were identified by the literature search. Meta-analysis of 26 biomarkers yielded 17 biomarkers that were differentially expressed in PAH and non-PH control subjects. Red cell distribution width, low density lipid-cholesterol, d-dimer, N-terminal prohormone of brain natriuretic protein (NT-proBNP), interleukin-6 (IL-6) and uric acid were biomarkers with the largest observed differences, largest sample sizes and a low risk of publication bias. Receiver operating characteristic curves and sensitivity/specificity analyses demonstrated that NT-proBNP had a high sensitivity, but low specificity for PAH. For the other biomarkers, insufficient data on diagnostic accuracy with receiver operating characteristic curves were available for meta-analysis. Conclusion: This meta-analysis validates NT-proBNP as a biomarker with high sensitivity for PAH, albeit with low specificity. The majority of biomarkers evaluated in this meta-analysis lacked either external validation or data on diagnostic accuracy. Further validation studies are required as well as studies that test combinations of biomarkers to improve specificity. Meta-analysis of 26 biomarkers yielded 17 differentially expressed biomarkers in PAH. NT-proBNP had the highest diagnostic accuracy but had a low specificity for PAH. Other markers, including IL-6, RDW, LDL-c, D-dimer and UA, lacked clinical validation. https://bit.ly/3J4YAyC